2012
DOI: 10.4236/as.2012.36097
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of anaerobically-digested and conventional liquid swine manure, and N fertilizer on crop yield and greenhouse gas emissions

Abstract: ABSTRACT). On average, agronomic performance of ADSM was similar to CTSM. The APNU of N fertilizer was greater than the 3× rate but lower than the 1× rate of ADSM or CTSM. Ammonia loss from ADSM was similar to CTSM, except for much higher loss of NH 3 -N from CTSM at the 3× rate applied in the autumn (8100 g·N·ha ). The percentage of applied N lost as N 2 O gas was generally higher for treatments receiving CTSM (4.0%) compared to ADSM (1.4%). In conclusion, the findings suggest that ADSM is equal or slightly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The liquid permeate was recirculated to the hydrolysis reactor for further use. The CVD SBO was characterized as previously reported . Table reports chemical composition details.…”
Section: Experimental Methodologysupporting
confidence: 92%
See 1 more Smart Citation
“…The liquid permeate was recirculated to the hydrolysis reactor for further use. The CVD SBO was characterized as previously reported . Table reports chemical composition details.…”
Section: Experimental Methodologysupporting
confidence: 92%
“…In principle, a broad range of effects may affect the N balancing results. These are precipitation of N‐containing substances like struvite on the bottom, walls and installations of the reactors, gaseous losses of ammonia‐N between sampling and analysis of fermentation liquor, and gaseous losses of other N‐containing gases . Under the experimental conditions of this work, the total mass contained in the reactors was recovered, the solid phase and liquid phases were separated, and each phase was analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Clemens et al (2006) found that cattle AD in Germany produced lower N 2 O emissions after field application compared with cattle RM and calcium ammonium nitrate over a 56 d period in pastures. Similarly, in a study performed in Saskatchewan (Canada), Lemke et al (2012) reported a reduction in N 2 O emissions after fall application of swine AD compared with swine RM. In contrast, Amon et al (2006) found no significant differences in N 2 O emissions between AD and untreated cattle slurry after applying approximately 100 kg N ha −1 in late summer.…”
Section: Introductionmentioning
confidence: 78%
“…Fall application of liquid raw dairy manure has been proven to increase N 2 O emissions when compared with no nitrogen (N) application (Wagner-Riddle et al 1997;Rochette et al 2000;Hao et al 2001;Kariyapperuma et al 2012;Cambareri et al 2017). However, anaerobically digesting the manure may be a mitigation strategy that could be used to reduce N 2 O emissions (Clemens et al 2006;Lemke et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation